2017
DOI: 10.1161/jaha.116.004823
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Is Associated With Increased Infarct Size and Decreased Myocardial Salvage in Patients With ST‐Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: BackgroundApproximately one third of patients with ST‐segment elevation myocardial infarction (STEMI) have left ventricular hypertrophy (LVH), which is associated with impaired outcome. However, the causal association between LVH and outcome in STEMI is unknown. We evaluated the association between LVH and: myocardial infarct size, area at risk, myocardial salvage, microvascular obstruction, left ventricular (LV) function (all determined by cardiac magnetic resonance [CMR]), and all‐cause mortality and readmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
1
23
0
3
Order By: Relevance
“…The CMR protocol and the image analyses have previously been described in detail. 17 Patients without CMR-related exclusion criteria underwent an in-hospital CMR examination during the index admission, following the primary PCI, and a follow-up examination approximately three months later to assess acute and final infarct size, acute and final myocardial salvage index, acute and final LVEF and MVO. Both CMR examinations were performed on a 1.5 T scanner (Siemens, Erlangen, Germany) using a six-channel body array coil.…”
Section: Cmr Imagingmentioning
confidence: 99%
“…The CMR protocol and the image analyses have previously been described in detail. 17 Patients without CMR-related exclusion criteria underwent an in-hospital CMR examination during the index admission, following the primary PCI, and a follow-up examination approximately three months later to assess acute and final infarct size, acute and final myocardial salvage index, acute and final LVEF and MVO. Both CMR examinations were performed on a 1.5 T scanner (Siemens, Erlangen, Germany) using a six-channel body array coil.…”
Section: Cmr Imagingmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH), an increase in muscle mass of left ventricle, has been identified as a powerful risk factor for future cardiovascular morbidity and mortality, with the risk of cardiovascular events increasing six-fold to eightfold [3]. In addition, LVH is independently associated with a higher risk of all-cause mortality and a higher incidence of heart failure in CAD patients treated with percutaneous coronary intervention (PCI) [4][5][6]. LVH can develop myocytes death and fibrotic remodeling, and this promotes cardiac dysfunction [7], leading to cardiac hypoxia [8].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that left ventricular hypertrophy (LVH) is an independent predictor of cardiovascular events and increases the risk of acute myocardial infarction (AMI) . LVH is present in approximately one‐third patients with AMI and is causally related to increased morbidity and mortality following AMI . Moreover, experimental studies have shown that animals with LVH have expanded myocardial infarct size and are refractory to cardioprotective treatments due to defective cytoprotective mechanisms following myocardial ischaemia–reperfusion (MI/R) .…”
Section: Introductionmentioning
confidence: 99%